2016
DOI: 10.1016/j.meatsci.2015.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Selection of a chitosan gelatin-based edible coating for color preservation of beef in retail display

Abstract: Chitosan gelatin-based coating films were applied to beef steaks, and their effects on color preservation and lipid oxidation during retail display were evaluated. Response surface methodology was used to model and describe the effects of different biopolymer concentrations (0 to 6% gelatin; 0.5 to 1.5% chitosan; and 0 to 12% glycerol based on dry gelatin+chitosan weight) in the coating film for optimizing the best combination for meat application. Film application reduced weight loss and lipid oxidation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
1
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(74 citation statements)
references
References 34 publications
4
62
1
7
Order By: Relevance
“…Wang et al found that pork slices wrapped with a chitosan film containing cinnamon oil‐ginger oil showed higher weight loss than the control sample (unwrapped) over 9 days of refrigerated storage. However, Cardoso et al observed a reduction in weight loss in beef steaks coated with chitosan‐gelatin film during storage in a refrigerator for 5 days. They also reported that the lower water solubility of the chitosan‐gelatin film might have contributed to the higher water barrier.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al found that pork slices wrapped with a chitosan film containing cinnamon oil‐ginger oil showed higher weight loss than the control sample (unwrapped) over 9 days of refrigerated storage. However, Cardoso et al observed a reduction in weight loss in beef steaks coated with chitosan‐gelatin film during storage in a refrigerator for 5 days. They also reported that the lower water solubility of the chitosan‐gelatin film might have contributed to the higher water barrier.…”
Section: Resultsmentioning
confidence: 99%
“…Level of lipid oxidation in the products was assessed by measuring the TBARS proposed by RAHARJO et al, (1992), with modifications described by CARDOSO et al, (2016).…”
Section: Methodsmentioning
confidence: 99%
“…Among different materials, chitosan, a polysaccharide deriving from deacetylation of chitin, is considered one of the best polymers due to absence of toxicity and its high biodegradability and antimicrobial activity (No et al, ). Chitosan‐based coatings are reported to extend the shelf life and to reduce the postharvest disease of different fruits, such as sweet cherry (Petriccione et al, ), tomato (Zhang, Wang, Hu, & Liu, ), mango (Jongsri, Wangsomboondee, Rojsitthisak, & Seraypheap, ; Prashanth, Baskaran, DhanyaSri, & Rajashekaramurthy, ), peach (Li & Yu, ), and table grape (Romanazzi, Lichter, Gabler, & Smilanick, ), in addition to other foods such as frozen salmon (Soares, Silva, Barbosa, Pinheiro, & Vicente, ) and beef steaks (Cardoso et al, ).…”
Section: Introductionmentioning
confidence: 99%